Inklusivitas Dalam Gereja : Pendekatan Pastoral Konseling Bagi Jemaat Dengan Disabilitas - Bokko, Lanny Sonia; Luma, Subaedah (PT. Giat Konseling Nusantara, 2024)
This article explores the concept of church inclusivity towards people with disabilities with a focus on the role and approach of pastoral counseling. Inclusivity is defined as the recognition and appreciation of diversity, including individuals with disabilities. The concept of pastoral counseling is discussed, emphasizing the importance of the church to provide support and approaches from the emotional, spiritual, and facilities support on the needs of congregants with disabilities. This research emphasizes the importance of disability inclusivity in the church context, with the important role of pastoral counseling in supporting individuals with disabilities to live fully and meaningfully in the community without feeling neglected by the church.